PRINSIP MONOMIALITY DAN FUNGSI EIGEN DARI OPERATOR DIFERENSIAL - Ade Fitri; Efendi . (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
Let Apn(x) = pn(x), where A is the dierential operator, is constant, andpolynomial pn(x) as the eigenfunction, has nontrivial solution, In this journal, the mono-miality principle can be used to determine the eigenfunction of the dierential operator.Moreover, some special polynomials are given and some eigenfunctions of dierensialoperator will be determined.